Experience of using a combination mucoactive drug during chemotherapy in patients with MDR/XDR tuberculosis - E. P. Myshkova; S. V. Sklyuev; E. M. Zhukova; D. V. Krasnov; T. I. Petrenko (Туберкулез и болезни лёгких)
The objective: to evaluate the effectiveness of the medication containing a 7% NaCl solution and 0.1% sodium hyaluronate in patients with destructive pulmonary tuberculosis and multiple/extensive drug resistance (MDR/XDR) and inflammatory changes in the tracheobronchial tree. Subjects and methods. A prospective randomized controlled study was carried out, which included 69 patients with destructive pulmonary tuberculosis and MDR/XDR and respiratory complaints and changes in the tracheobronchial tree detected by fibrobronchoscopy. All patients underwent a complete clinical and functional examination, and by analyzing the questionnaires, the mMRC dyspnea index was calculated, the CAT test was performed, and the response to treatment was assessed using the Likert scale. The patients were randomly divided into two groups. The main group included 30 patients; in addition to anti-tuberculosis therapy, through a nebulizer, they received inhalation with the solution containing 7% NaCl and 0.1% sodium hyaluronate, 5 ml 2 times a day for 10 consecutive days, 20 inhalations. The control group (39 people) received individual chemotherapy according to the resistance profile with standard mucolytic treatment. The examination was carried out before the course with the mucoactive drug (visit I), then at the end of the course – after 10 days (visit II) and after 30 days (visit III) from the moment of inclusion in the study. The significance of differences (p) was determined at p <0.05 using χ² Pearson, Fisher's exact test, Mann-Whitney test, and paired Wilcoxon test. Results. There was an increase in the effectiveness of treatment of patients in this category according to the following criteria: disappearance or decrease of respiratory symptoms (on the 10th day from the start of treatment), early regression of inflammatory changes in the tracheobronchial tree (on the 30th day from the start of treatment in 24 (73.4%) patients in the main group, in 10 (25.1%) patients in the comparison group (RR = 3.34; 95% CI 2.78-3.90)].